Negative electrode material and preparation method and application thereof

A core-shell structured silicon-based negative electrode material with carbon-nitrogen and lithium phosphate coatings addresses mechanical stress issues, improving lithium ion conductivity and cycle stability in lithium-ion batteries.

CN119170759AActive Publication Date: 2024-12-20CHONGQING INNOVATION CENTER OF BEIJING INSTITUTE OF TECHNOLOGY +1

Patent Information

Application Number
CN202410923441.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-10
Publication Date
2024-12-20
Estimated Expiration
2044-07-10

AI Technical Summary

Technical Problem

Silicon-based negative electrode materials in lithium-ion batteries suffer from poor mechanical properties due to volume expansion during lithiation and delithiation, leading to SEI film rupture, low first coulombic efficiency, rapid capacity decay, and poor cycle stability.

Method used

A core-shell structured negative electrode material with a silicon-based core and sequential carbon-nitrogen and lithium phosphate coating layers, designed to enhance mechanical properties and stability, is developed.

Benefits of technology

The dual coating layer structure improves the structural stability, enhances lithium ion conductivity, and increases the first cycle efficiency and cycle stability of the negative electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170759A_ABST
    Figure CN119170759A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and discloses a negative electrode material and a preparation method and application thereof.The negative electrode material is of a core-shell structure, an inner core is silicon-based particles, and a shell comprises a first coating layer and a second coating layer; the first coating layer is attached to the outside of the inner core, and the second coating layer is attached to the outside of the first coating layer; the first coating layer comprises a carbon nitrogen compound, and the second coating layer comprises phosphate. The negative electrode material provided by the invention takes the silicon-based particles as the inner core, the carbon-nitrogen coating layer and the phosphate coating layer are sequentially attached outside the inner core, and under the action of the double coating layers, the lithium ion conductivity and the electrochemical performance of the negative electrode material are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a negative electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, lithium-ion batteries (LIBs) are not only required to have a long cycle life and be green and environmentally friendly, but also to have a high energy / power density. At present, the theoretical lithium insertion capacity of graphite anode is only 372mAh / g, which seriously limits the further improvement of lithium-ion battery energy density and cannot meet the rapidly developing market demand. Therefore, it is very necessary to develop anode materials with high energy density, durability and long cycle life.

[0003] Silicon-based materials are considered to be one of the most attractive negative electrode materials for lithium-ion batteries because they have a high theoretical capacity (up to 3579mAh / g, about 10 times that of graphite), are rich in silicon, and are relatively cheap. However, silicon has a large volume expansion (about 300%) during lithiation and delithiation, which will cause the solid electrolyte interface (SEI) film to break and regenerate during the cycle, and the particles to break or even pulverize. Therefore, during the cycle, the silicon-based material has a low first coulomb efficiency, a fast capacity decay, and poor cycle stability.

[0004] The first coulomb efficiency (hereinafter referred to as the first efficiency) is an important indicator to measure the charging and discharging capacity of lithium-ion batteries. As the silicon content increases, the first efficiency will become lower and lower, and the conventional effective method to improve the first efficiency is pre-lithiation, that is, adding a small amount of lithium to the negative electrode in advance to replenish the lithium consumed in the side reaction and the formation of the solid electrolyte interface (SEI) film. However, in order to achieve high-capacity pre-lithiation in lithium batteries, it is necessary to produce very thin lithium foil (less than 5μm thick), which brings great technical difficulties. In addition, when using thin lithium foil for pre-lithiation, the utilization efficiency of lithium metal is not high, and lithium metal fragments may be generated, affecting the performance and service life of the battery.

[0005] In order to solve the above problems, a coating process for the base material is adopted. The coating processes reported so far are mostly limited to single-layer coating, and usually ignore the design of the mechanical properties (elasticity, rigidity, toughness, etc.) of the coating layer, which is particularly important for the regulation of stress and strain of the electrode. Ignoring the design of mechanical properties leads to poor mechanical properties of the coating layer, which cannot adapt to the severe stress and strain during the lithiation / delithiation process, and the electrochemical performance of the coated electrode material is not satisfactory.

[0006] Therefore, there is an urgent need to provide a negative electrode material with excellent mechanical properties that can withstand the stress caused by volume expansion of silicon-based negative electrode materials during lithiation, improve the structural stability of the SEI film, and thus improve the material's first coulombic efficiency, capacity attenuation performance and cycle stability. Summary of the invention

[0007] The purpose of the present invention is to overcome the problems of poor mechanical properties of silicon-based materials in the prior art, which cannot adapt to the severe stress generated by the volume expansion of silicon during lithiation and delithiation, resulting in rupture or crushing of the SEI film, resulting in low first coulombic efficiency, rapid capacity decay and poor cycle stability of silicon-based negative electrode materials.

[0008] In order to achieve the above object, the present invention provides a negative electrode material in a first aspect, wherein the negative electrode material is a core-shell structure, the core is a silicon-based particle, and the shell includes a first coating layer and a second coating layer;

[0009] Wherein, the first coating layer is attached to the outside of the inner core, and the second coating layer is attached to the outside of the first coating layer;

[0010] Wherein, the first coating layer includes carbonitride, and the second coating layer includes phosphate.

[0011] A second aspect of the present invention provides a method for preparing a negative electrode material, wherein the method comprises the following steps:

[0012] (1) mixing silicon-based particles, a dopant, an oxidant and a nitrogen-containing heterocyclic compound monomer in an organic solvent, and drying the mixture to obtain a gray-brown powder;

[0013] (2) The gray-brown powder is heat-treated with phosphate in an acidic solution to obtain a negative electrode material.

[0014] The third aspect of the present invention provides a negative electrode material prepared by the method of the present invention.

[0015] A fourth aspect of the present invention provides use of the negative electrode material of the present invention in a lithium ion battery.

[0016] Through the above technical solution, the present invention achieves the following beneficial technical effects:

[0017] (1) The silicon-based particles used in the present invention are micrometer-sized, and the preparation process is simpler and the cost is lower than that of nanometer-sized silicon-based particles.

[0018] (2) The negative electrode material provided by the present invention has a silicon-based particle as the core, and a carbon-nitrogen coating layer and a lithium phosphate coating layer are sequentially attached to the outside of the core, wherein the carbon-nitrogen coating layer has strong flexibility and viscosity, and can absorb the residual stress transmitted by the rigid coating layer, further improving the stability of the structure; the lithium phosphate coating layer has excellent mechanical properties, improves the cycle stability of the negative electrode material, and can ensure the rapid transmission of ions / electrons, and improve the rate performance of the negative electrode material. Under the action of the double coating layer, the lithium ion conductivity and electrochemical performance of the negative electrode material are effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The scanning electron microscope test (SEM) images of the negative electrode materials A1 and B1-B3 prepared in Example 1 and Comparative Examples 1-3 are respectively;

[0020] Figure 1 a-1d correspond to the samples of Si@NC@LPO in Example 1, Si@NC in Comparative Example 1, Si@LPO in Comparative Example 2, and Si@LPO@NC in Comparative Example 3, respectively.

[0021] Figure 2 Energy X-ray spectrum test (EDS) diagrams of negative electrode materials A1 and B1-B3 prepared in Example 1 and Comparative Examples 1-3, respectively;

[0022] Figure 2 a-2d correspond to the samples of Si@NC@LPO in Example 1, Si@NC in Comparative Example 1, Si@LPO in Comparative Example 2, and Si@LPO@NC in Comparative Example 3, respectively.

[0023] Figure 3 The first cycle charge-discharge curves of button batteries C1, D1-D3 prepared with negative electrode materials A1 and B1-B3 prepared in Example 1 and Comparative Examples 1-3 as negative electrode active materials, respectively, obtained by cycling at 0.01-1.5V, 0.1C;

[0024] Figure 3 a-3d correspond to button batteries C1 and D1-D3 prepared with Si@NC@LPO in Example 1, Si@NC in Comparative Example 1, Si@LPO in Comparative Example 2, and Si@LPO@NC in Comparative Example 3 as negative electrode active materials.

[0025] Figure 4 The charge-discharge cycle curves of button batteries C1, D1-D3 prepared with negative electrode materials A1 and B1-B3 prepared in Example 1 and Comparative Examples 1-3 as negative electrode active materials at 0.01-1.5V, 1C;

[0026] Figure 4a-4d correspond to button batteries C1 and D1-D3 prepared with Si@NC@LPO in Example 1, Si@NC in Comparative Example 1, Si@LPO in Comparative Example 2, and Si@LPO@NC in Comparative Example 3 as negative electrode active materials.

[0027] Figure 5 This is a scanning electron microscope (SEM) image of the micron silicon particles in Comparative Example 4.

[0028] Figure 6 The first cycle charge and discharge curve of the button battery D4 prepared with the micron silicon in Comparative Example 4 as the negative electrode active material is obtained by cycling at 0.01-1.5V and 0.1C.

[0029] Figure 7 The charge and discharge cycle curve of button battery D4 prepared with micron silicon in comparative example 4 as negative electrode active material at 0.01-1.5V and 1C. DETAILED DESCRIPTION

[0030] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0031] The first aspect of the present invention provides a negative electrode material, wherein the negative electrode material is a core-shell structure, the core is a silicon-based particle, and the shell includes a first coating layer and a second coating layer;

[0032] Wherein, the first coating layer is attached to the outside of the inner core, and the second coating layer is attached to the outside of the first coating layer;

[0033] Wherein, the first coating layer includes carbonitride, and the second coating layer includes phosphate.

[0034] According to some embodiments of the present invention, the silicon-based particles have a particle size of 1-5 μm.

[0035] According to some embodiments of the present invention, the phosphate is selected from lithium phosphate and / or lithium dihydrogen phosphate, preferably lithium phosphate.

[0036] In the present invention, the type of phosphate satisfies the above range, which can provide a coating layer with a certain rigidity and improve the mechanical properties of the coating layer.

[0037] In the present invention, the carbon-nitrogen compound is prepared by carbonizing a polymer.

[0038] Preferably, the polymer is selected from at least one of polypyrrole and / or polyaniline, more preferably polypyrrole.

[0039] In the present invention, the negative electrode material has silicon-based particles as the core, and carbon-nitrogen coating layers and lithium phosphate coating layers are sequentially attached to the outside of the core, wherein the carbon-nitrogen coating layer, as a flexible layer, has strong flexibility and viscosity, can absorb the residual stress transmitted by the rigid coating layer, and further improve the stability of the structure; the lithium phosphate coating layer, as a rigid layer, has excellent mechanical properties, can resist the stress caused by the volume expansion of the silicon-based negative electrode during the lithiation process, further improve the stability of the material structure, thereby improving the first cycle efficiency; at the same time, it avoids irreversible deformation and fracture of the SEI film, maintains the integrity of the SEI film structure, improves the lithium ion conductivity of the material during the charge and discharge process, and thus improves the rate performance of the material. Under the action of the double coating layer, the lithium ion conductivity of the negative electrode material and the electrochemical performance of the negative electrode material are effectively improved.

[0040] A second aspect of the present invention provides a method for preparing a negative electrode material, wherein the method comprises the following steps:

[0041] (1) mixing silicon-based particles, a dopant, an oxidant and a pyrrole monomer in an organic solvent, and drying the mixture to obtain a gray-brown powder;

[0042] (2) The gray-brown powder is heat-treated with phosphate in an acidic solution to obtain a negative electrode material.

[0043] According to some embodiments of the present invention, the molar ratio of the dopant, the nitrogen-containing heterocyclic compound and the oxidant is 1:(1-3):(6-9).

[0044] According to some embodiments of the present invention, the nitrogen-containing heterocyclic compound is selected from pyrrole and / or aniline, preferably pyrrole.

[0045] According to some embodiments of the present invention, the organic solvent is anhydrous ethanol.

[0046] According to some embodiments of the present invention, the dopant is selected from at least one of sodium p-toluenesulfonate, sodium dodecylsulfonate and sodium dodecylbenzenesulfonate, preferably sodium p-toluenesulfonate.

[0047] According to some embodiments of the present invention, the oxidant is selected from ferric chloride and / or ferrous chloride, preferably ferric chloride.

[0048] In the present invention, silicon-based particle powder is used as raw material, sodium p-toluenesulfonate is used as a dopant, and ferric chloride is used as an oxidant to initiate in-situ polymerization of pyrrole monomer to generate polypyrrole, which is attached to the outside of the silicon-based particles. After heat treatment, the polypyrrole is carbonized into a carbon-nitrogen coating layer that is uniformly attached to the silicon-based particles, thereby providing a flexible and sticky carbon-nitrogen coating layer to improve the stability of the negative electrode material structure.

[0049] According to some embodiments of the present invention, the acidic solution is a mixed solution of formic acid and water.

[0050] Preferably, the volume ratio of formic acid to water is (1-5):100.

[0051] According to some embodiments of the present invention, the mass ratio of the silicon-based particles to the phosphate is (5-25):1.

[0052] According to some embodiments of the present invention, in step (1), the mixing method comprises: performing magnetic stirring under ice bath conditions.

[0053] Preferably, the temperature of the ice bath is 0-3°C; the conditions for magnetic stirring include: a rotation speed of 200-300 r / min, and a time of 6-8 h.

[0054] According to some embodiments of the present invention, in step (1), the drying temperature is 60-80° C. and the drying time is 11-12 h.

[0055] In the present invention, in step (2), before the heat treatment, a heating and grinding treatment is further included, and the specific method includes: mixing and dispersing the gray-brown powder and the phosphate in an acidic solution, heating the solution to dryness under magnetic stirring, collecting the solid product and grinding it to obtain a dark brown powder. Preferably, the heating temperature is 60-80°C.

[0056] According to some embodiments of the present invention, in step (2), the heat treatment method comprises: heating to 300-500°C at a heating rate of 5-10°C / min in an argon atmosphere, and heat treating for 3-6 hours.

[0057] In the present invention, the above method can adjust the inner and outer order of the carbon-nitrogen coating layer and the phosphate coating layer attached to the outer shell of the silicon-based material to form a "soft inside and hard outside" coating layer. Due to its unique dual energy absorption mechanism, it effectively avoids the particle breakage of the silicon-based negative electrode material during the cycle process, improves the structural stability of the negative electrode material during the cycle process, and thus improves the first cycle efficiency of the negative electrode material.

[0058] The third aspect of the present invention provides a negative electrode material prepared by the method of the present invention.

[0059] A fourth aspect of the present invention provides use of the negative electrode material of the present invention in a lithium ion battery.

[0060] The present invention will be described in detail below through examples.

[0061] Unless otherwise specified, all materials were commercially available.

[0062] Example 1

[0063] (1) 0.5 g of micron silicon powder (particle size of 1 μm) was dispersed in 40 mL of anhydrous ethanol, the silicon powder dispersion was placed in an ice bath, sodium p-toluenesulfonate, pyrrole monomer, and anhydrous ferric chloride were added respectively, and magnetic stirring was performed at 0°C for 6 h (speed of 250 r / min), and after centrifugation at 6000 r / min, a Si@PPy precursor was obtained, which was dried at 80°C for 12 h to obtain a gray-brown powder, namely, Si@PPy powder;

[0064] Wherein, the molar ratio of sodium p-toluenesulfonate, pyrrole monomer and anhydrous ferric chloride is 1:3:9;

[0065] (2) Add 2 g of Si@PPy powder and 0.1 g of lithium phosphate to a mixed solution of 1000 μL of formic acid and 100 ml of water (the volume ratio of formic acid to water is 1:100), mix thoroughly, and stir magnetically at 80 °C until the solution evaporates to dryness. Collect the solid product and grind it to obtain a dark brown powder.

[0066] (3) The dark brown powder was transferred to a tube furnace, heated to 400°C at a rate of 5°C / min in an argon atmosphere, and heat treated for 6 hours to obtain Si@NC@LPO powder, i.e., the negative electrode material A1 was prepared;

[0067] Among them, the prepared negative electrode material A1 has a carbon-nitrogen coating layer and a lithium phosphate coating layer attached in sequence outside the silicon-based particles.

[0068] Comparative Example 1

[0069] (1) 0.5 g of silicon powder was dispersed in 40 mL of ethanol, sodium p-toluenesulfonate and pyrrole monomer were added respectively, and ultrasonic treatment was performed for 10 min. FeCl3 was dissolved in 20 mL of ethanol, and the silicon powder dispersion was stirred in an ice bath, and FeCl3 ethanol solution was added, and stirred at 0°C for 6 h (speed of 250 r / min). After centrifugation at 6000 r / min, Si@PPy precursor was obtained, and dried at 80°C for 12 h to obtain gray-brown powder, namely Si@PPy powder;

[0070] Wherein, the molar ratio of sodium p-toluenesulfonate, pyrrole monomer and anhydrous ferric chloride is 1:3:9;

[0071] (2) The gray-brown powder was transferred to a tube furnace, heated to 400°C at a rate of 5°C / min in an argon atmosphere, and heat treated for 6 hours to obtain Si@NC powder, i.e., the negative electrode material B1 was prepared;

[0072] Among them, the prepared negative electrode material B1 has only a carbon-nitrogen coating layer attached to the outside of the silicon-based particles.

[0073] Comparative Example 2

[0074] (1) In a mixed solution of 1000 μL formic acid and 100 ml water (the volume ratio of formic acid to water is 1:100), 2 g of micron silicon powder and 0.1 g of lithium phosphate were added, and after thorough mixing, magnetic stirring was performed at 80° C. until the solution was evaporated to dryness, and the solid product was collected and ground to obtain a dark brown powder;

[0075] (2) The dark brown powder was transferred to a tube furnace, heated to 400°C at a rate of 5°C / min in an argon atmosphere, and heat treated for 6 hours to obtain Si@LPO powder, i.e., the negative electrode material B2 was prepared;

[0076] Among them, the prepared negative electrode material B2 has only a lithium phosphate coating layer attached to the outside of the silicon-based particles.

[0077] Comparative Example 3

[0078] (1) In a mixed solution of 1000 μL formic acid and 100 ml water (the volume ratio of formic acid to water is 1:100), 2 g of micron silicon powder and 0.1 g of lithium phosphate were added, and after thorough mixing, magnetic stirring was performed at 80° C. until the solution was evaporated to dryness, and the solid product was collected, ground, and dried at 80° C. for 12 h to obtain a dark brown powder, i.e., Si@LPO powder;

[0079] (2) 0.5 g of dark brown powder was dispersed in 40 mL of anhydrous ethanol, sodium p-toluenesulfonate and pyrrole monomer were added respectively, and ultrasonication was performed for 10 min. FeCl3 was dissolved in 20 mL of ethanol, the silicon powder dispersion was stirred in an ice bath, and FeCl3 ethanol solution was added, stirred at 0 ° C for 6 h (speed of 250 r / min), and after centrifugation at 6000 r / min, Si@LPO@PPy precursor was obtained;

[0080] Wherein, the molar ratio of sodium p-toluenesulfonate, pyrrole monomer and anhydrous ferric chloride is 1:3:9;

[0081] (3) The Si@LPO@PPy precursor was transferred to a tube furnace, heated to 400°C at a rate of 5°C / min under an argon atmosphere, and heat treated for 6 hours to obtain Si@LPO@NC powder, i.e., the negative electrode material B3 was prepared;

[0082] Among them, the prepared negative electrode material B3 has a lithium phosphate coating layer and a carbon nitrogen coating layer attached in sequence outside the silicon-based particles.

[0083] Comparative Example 4

[0084] Micron silicon particles (particle size of 1 μm) were used as negative electrode material B4, and there was no coating layer outside the silicon-based particles.

[0085] Test Example 1

[0086] The negative electrode materials A1, B1-B4 (Si@NC@LPO, Si@NC, Si@LPO, Si@LPO@NC and micron silicon particles) in Example 1 and Comparative Examples 1-4 were respectively used as negative electrode active materials, Super P was used as a conductive agent, and PAA-Li was used as a binder. The three were mixed in a mass ratio of 8:1:1, and water was used as a solvent. The electrode slurry was obtained by grinding in an agate mortar for 30 minutes. Copper foil was used as a current collector, and the electrode slurry was coated on the copper foil, transferred to a vacuum drying oven, vacuum dried at 80°C for 12 hours, and then taken out, and a circular electrode sheet with a diameter of 11 mm was obtained by punching using a sheet cutting machine. The prepared electrode was used as the negative electrode, the lithium sheet as the counter electrode, celgard2500 as the separator, and an organic solvent of EC+DMC (volume ratio 1:1) containing 1 mol / L LiPF6 and 5% FEC as the electrolyte. CR2032 button batteries C1, D1-D4 were assembled in a glove box filled with argon atmosphere.

[0087] The above CR2032 button batteries C1, D1-D4 were subjected to scanning electron microscope (SEM) test and energy dispersive X-ray spectroscopy (EDS) test respectively. At the same time, the electrochemical performance test of the assembled batteries was carried out on the LAND battery test system. The results are as follows: Figure 1-7 shown.

[0088] Energy dispersive X-ray spectroscopy (EDS) test: an energy dispersive X-ray fluorescence spectrometer produced by Oxford was used, and the instrument model was Oxford X-MAX.

[0089] Figure 1 The scanning electron microscope test (SEM) images of the negative electrode materials A1 and B1-B3 prepared in Example 1 and Comparative Examples 1-3 are respectively. Figure 1 a-1d correspond to the scanning electron microscope (SEM) images of Si@NC@LPO in Example 1, Si@NC in Comparative Example 1, Si@LPO in Comparative Example 2, and Si@LPO@NC in Comparative Example 3, respectively. Figure 1 As shown, after the silicon-based particles in the Si@NC@LPO sample in Example 1 are double coated with a lithium phosphate coating layer and a carbon nitrogen coating layer, the surface of the material particles becomes denser.

[0090] Figure 2 They are energy X-ray spectrum test (EDS) graphs of negative electrode materials A1 and B1-B3 prepared in Example 1 and Comparative Examples 1-3, respectively. Figure 2 a-2d correspond to the energy X-ray spectrum test (EDS) diagrams of Si@NC@LPO in Example 1, Si@NC in Comparative Example 1, Si@LPO in Comparative Example 2, and Si@LPO@NC in Comparative Example 3, respectively. Figure 2 As shown, each element in each sample is evenly dispersed on the surface of the negative electrode material, indicating that the coating effect of the four samples in Example 1 and Comparative Examples 1-3 is good.

[0091] Figure 3 The first week charge and discharge curves of button batteries C1 and D1-D3 prepared with negative electrode materials A1 and B1-B3 prepared in Example 1 and Comparative Examples 1-3 as negative electrode active materials, respectively, are obtained by cycling at a current density of 0.1C (1C current density is 2000mA / g) in a voltage window of 0.01-1.5V. Figure 3 a- Figure 3 d respectively correspond to the first week charge and discharge curves of button cells C1 and D1-D3 prepared with Si@NC@LPO in Example 1, Si@NC in Comparative Example 1, Si@LPO in Comparative Example 2, and Si@LPO@NC in Comparative Example 3 as negative electrode active materials. Figure 3 It can be seen that the button battery prepared with the Si@NC@LPO sample in Example 1 as the negative electrode active material has a discharge capacity and a charge capacity of 3222.6 mAh / g and 2772.1 mAh / g in the first cycle, and a coulombic efficiency of 86.0% in the first cycle; the button battery prepared with the Si@NC sample in Comparative Example 1 as the negative electrode active material has a discharge capacity and a charge capacity of 3308.1 mAh / g and 2888.8 mAh / g in the first cycle, and a coulombic efficiency of 87 .3%; the button battery prepared with the Si@LPO sample in Comparative Example 2 as the negative electrode active material had a discharge capacity and a charge capacity of 3295.6 mAh / g and 2934.7 mAh / g in the first cycle, and a coulombic efficiency of 89.1% in the first cycle; the button battery prepared with the Si@LPO@NC sample in Comparative Example 3 as the negative electrode active material had a discharge capacity and a charge capacity of 3277.2 and 2823.4 mAh / g in the first cycle, and a coulombic efficiency of 86.2%.

[0092] Figure 4 The charge-discharge cycle curves of button batteries C1 and D1-D3 prepared with the negative electrode materials A1 and B1-B3 prepared in Example 1 and Comparative Examples 1-3 as negative electrode active materials, respectively, are shown in the voltage window of 0.01-1.5V and cycled 100 times at 1C. Figure 4a-4d correspond to button batteries C1 and D prepared with Si@NC@LPO in Example 1, Si@NC in Comparative Example 1, Si@LPO in Comparative Example 2, and Si@LPO@NC in Comparative Example 3 as negative electrode active materials, respectively. 1- The charge and discharge cycle data of D3 is given by Figure 4 It can be seen that after 100 stable cycles, the reversible specific capacities of Si@NC@LPO in Example 1, Si@NC in Comparative Example 1, Si@LPO in Comparative Example 2, and Si@LPO@NC in Comparative Example 3 are 1609.6 mAh / g, 1410.5 mAh / g, 1357.4 mAh / g, and 1328.0 mAh / g, respectively; the capacity retention rates from the 20th cycle are 91.1%, 98.9%, 88.9%, and 100%, respectively.

[0093] Figure 5 This is a scanning electron microscope (SEM) image of the micron silicon particles in Comparative Example 4. Figure 5 It can be seen that the particle size of the micron silicon particles is uneven, basically distributed in the range of 1-5 μm, the particle surface is rough, and there is agglomeration.

[0094] Figure 6 The first cycle charge and discharge curve of the button battery D4 prepared with micron silicon as the negative electrode active material in Comparative Example 4 was obtained by cycling at 0.01-1.5V and 0.1C. Figure 6 It can be seen that the button battery prepared with micron silicon as the negative electrode active material has a discharge capacity and a charge capacity of 3211.6 mAh / g and 2568.7 mAh / g respectively in the first cycle, and the coulombic efficiency in the first cycle is only 80.0%.

[0095] Figure 7 The charge and discharge cycle curve of button battery D4 prepared with micron silicon in comparative example 4 as negative electrode active material at 0.01-1.5V, 1C. Figure 7 It can be seen that the button battery prepared with micron silicon as the negative electrode active material has a reversible specific capacity of 1016.5 mAh / g after 100 stable cycles, and the capacity retention rate is 89.6%.

[0096] In summary, the negative electrode material prepared by the method of the present invention has a carbon-nitrogen coating layer and a lithium phosphate coating layer attached in sequence outside the silicon-based material, and the reversible specific capacity of the negative electrode material after a long cycle is higher.

[0097] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A negative electrode material, characterized in that: The negative electrode material is a core-shell structure, the core is a silicon-based particle, and the shell includes a first coating layer and a second coating layer; Wherein, the first coating layer is attached to the outside of the inner core, and the second coating layer is attached to the outside of the first coating layer; Wherein, the first coating layer includes carbonitride, and the second coating layer includes phosphate.

2. The negative electrode material according to claim 1, wherein The particle size of the silicon-based particles is 1-5 μm.

3. The negative electrode material according to claim 1 or 2, wherein The phosphate is selected from lithium phosphate and / or lithium dihydrogen phosphate, preferably lithium phosphate.

4. A method for preparing a negative electrode material, characterized in that: The method comprises the following steps: (1) mixing silicon-based particles, a dopant, an oxidant and a nitrogen-containing heterocyclic compound monomer in an organic solvent, and drying the mixture to obtain a gray-brown powder; (2) The gray-brown powder is heat-treated with phosphate in an acidic solution to obtain a negative electrode material.

5. The method according to claim 4, wherein: The molar ratio of the dopant, the nitrogen-containing heterocyclic compound and the oxidant is 1:(1-3):(6-9); And / or, the nitrogen-containing heterocyclic compound is selected from pyrrole and / or aniline, preferably pyrrole.

6. The method according to claim 4 or 5, wherein: The organic solvent is anhydrous ethanol; and / or, the dopant is at least one selected from sodium p-toluenesulfonate, sodium dodecylsulfonate and sodium dodecylbenzenesulfonate, preferably sodium p-toluenesulfonate; And / or, the oxidant is selected from ferric chloride and / or ferrous chloride, preferably ferric chloride.

7. The method according to any one of claims 4 to 6, wherein: The acidic solution is a mixed solution of formic acid and water; Preferably, the volume ratio of formic acid to water is (1-5):100; Preferably, the mass ratio of the silicon-based particles to the phosphate is (5-25):

1.

8. The method according to any one of claims 4 to 7, wherein: In step (1), the mixing method comprises: performing magnetic stirring under ice bath conditions; Preferably, the temperature of the ice bath is 0-3°C; the conditions for magnetic stirring include: a rotation speed of 200-300 r / min, and a time of 6-8 h; And / or, in step (1), the drying temperature is 60-80°C and the time is 11-12h; And / or, in step (2), the heat treatment method comprises: heating to 300-500°C at a heating rate of 5-10°C / min in an argon atmosphere, and heat treating for 3-6 hours.

9. A negative electrode material prepared by the method according to any one of claims 4 to 8.

10. Use of the negative electrode material according to any one of claims 1 to 3 and 9 in a lithium ion battery.

Citation Information

Patent Citations

  • Silicon-based composite material containing lithium phosphate coating layer constructed by in-situ conversion and preparation method of silicon-based composite material

    CN113422037A

  • Silicon-carbon composite material for secondary lithium battery and preparation method thereof

    CN113823772A

  • Negative electrode material, preparation method thereof and lithium ion battery

    CN117936726A

  • Lithium ion battery negative electrode material, preparation method thereof and lithium ion battery

    CN118263426A

  • Prelithiated negative electrodes including composite li-si alloy particles and methods of manufacturing the same

    US20220320493A1

Cited By

  • Lithium phosphate modified silicon-based anode material, preparation method thereof, lithium ion battery and anode electrode of lithium ion battery

    CN120914220A

  • Lithium phosphate modified silicon-based anode material, preparation method thereof, and lithium ion battery and anode electrode thereof

    CN120914220B

  • Preparation method of polypyrrole / lithium metaborate composite flexible layer / rigid layer co-coated nano silicon negative electrode material

    CN120978043A